Topical metronidazole and clotrimazole in the treatment of vulvo-vaginal infections during pregnancy - Lorenzo Pradelli (Clinical Management Issues, 2007)
Vulvo-vaginal infections are the most common gynaecological pathologies seen in clinical practice. While being predominantly benign, although disturbing, in non pregnant women, their presence during pregnancy has been associated with peri-natal and obstetric complications. The opportunity to prevent these adverse outcomes, especially prematurity and low birth weight, has to be cautiously balanced against the potential to induce fetal toxicity, inherently related to the continuous exchanges among maternal and fetal blood that occurs in the placenta. In this paper, a brief overview of the evidence regarding efficacy, safety and utility during pregnancy of topical clotrimazole and metronidazole, whose combined spectrum covers the great majority of the involved pathogens, is provided. These antimicrobials, especially when applied topically, are highly effective and have been used in pregnant women for many years without evidence of adverse outcomes; in conclusion it appears that they hold an adequate risk-to-benefit ratio and represent valid therapeutic options in the treatment of vulvo-vaginal infections during pregnancy.